Perspectives of ammonite paleobiology from shell abnormalities in the genus Baculites - Henderson, R; Kennedy, W; Cobban, W (2002)
Many Baculites specimens from the Upper Cretaceous of the United States Western Interior show exceptional preservation of the original aragonitic shell and its fine-scale surface ornamentation. Growth lines are ubiquitous, with two orders of these structures represented on some shells, and reflect the incremental addition of new shell at the apertural margin. Growth line interruption in the form of repair of minor shell damage at the aperture, commonplace in contemporary Nautilus, is essentially absent in Baculites, suggesting that its members fed on small prey in the water column. As typical of Mesozoic ammonites in general, and in striking contrast to contemporary Nautilus, no in vivo epizoans have been recognized on specimens of Baculites. It is inferred that the shell of Baculites was covered in periostracum to eliminate epizoic colonization. By analogy with Nautilus, a distinctive micro-ornament oriented at right angles to growth lines and visible on parts of some specimens was probably associated with periostracal attachment. A small proportion of Baculites specimens show abnormalities in shell growth categorized as v-shaped indentations of growth lines, shell grooves, fine-scale folds on the surface of growth lines and feather structures. We view this entire set of structures as due to abnormalities in mantle growth induced at the leading edge, impressed into the periostracum during its fabrication, and then in turn into the shell surface. As many of the Baculites with shell abnormalities are smooth, the proposal by Checa linking homologous structures recognized on other ammonites to the formation of comarginal ribs is rejected. A case of sutural inversion, in which the form of minor divisions of the major saddles and lobes are transposed, is recognized in a specimen of Baculites codyensis Reeside. We consider sutural pattern in ammonites, an expression of septal fluting, as replicating the genetically specified standing form of an elastic adapical visceral mass. The inverted sutural pattern, and by implication the style of septal fluting, was transcribed exactly in the three successive septa preserved on the specimen. The abnormality appears to be a case of homeotic mutation in which the plan for one body region becomes translocated to another. The conservatism of major elements of sutural (=septal) patterns for Mesozoic ammonites in their evolutionary spectrum suggests that a homeobox of conserved DNA sequence, with the transcription factors encoded in homeotic genes, is likely to have been involved. Ammonites, growth, ornament, septa.